PJOK Learning: How to Apply Animation Media Based on Contextual Approach? - Ari Gunardi; Elsa Ariestika (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the application of contextual approach-based animation media in Physical, Sport, and Health Education (PJOK) learning for fourth-grade elementary school students. This research is a development method that refers to the ADDIE model. ADDIE development research consists of five stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The data analysis technique of this research uses the results of the review of learning content experts, learning design experts, and media experts in the form of input, feedback, criticism, and suggestions for improvement contained in the questionnaire and the percentage score. The results showed that the learning animation media based on the contextual approach PJOK for fourth-grade elementary school students produced learning products suitable for the learning process. Thus, this study concludes that by learning resources using animated media based on a contextual approach, students are more enthusiastic by having a high interest in learning.